Endocrinological aspects of pituitary adenoma surgery in Europe - Netuka, David; Grotenhuis, André; Foroglou, Nicolas; Zenga, Francesco; Froehlich, Sebastien; Ringel, Florian; Sampron, Nicolas; Thomas, Nick; Komarc, Martin; Kosák, Mikuláš; Májovský, Martin (Scientific reports, 2022)
Hormone-secreting adenomas are treated in many neurosurgical centers within Europe. The goal of the survey is to understand variance in practice management of pituitary tumors amongst neurosurgical centers. A list of departments performing pituitary surgery was created. The survey consisted of 58 questions. This study focuses on neurosurgical care of hormone-secreting adenomas. For analysis, the departments were divided into four subgroups: academic/non-academic, high-volume/low-volume, "mainly endoscopic/mainly microscopic practice" and geographical regions. Data from 254 departments from 34 countries were obtained. Most centers surgically treat 1-5 hormone-secreting adenomas per year. In prolactinomas this is the case in 194 centers, (76.4%), in GH-secreting adenomas: 133 centers, (52.4%), ACTH-secreting adenomas: 172 centers, (69.8%). Surgery as a primary treatment of prolactinomas is considered in 64 centers (25.2%). In 47 centers (18.8%), GH-secreting microadenomas are often treated pharmacologically first. Debulking surgery for an invasive GH-secreting adenoma in which hormonal remission is not a realistic goal of the surgery and the patient has no visual deficit surgery is always or mostly indicated in 156 centers (62.9%). Routine postoperative hydrocortisone replacement therapy is administered in 147 centers (58.6%). Our survey shows that in most centers, few hormone-secreting adenomas are treated per year. In about 25% of the centers, prolactinoma surgery may be regarded as first-line treatment; in about 20% of the centers, medical treatment is the first-line treatment for GH-secreting adenomas. Pretreatment for ACTH-secreting adenomas is routinely used in 21% of centers. This survey may serve as plea for neurosurgical care centralization of hormone-secreting adenomas.
Keywords: Prolactinoma; Pituitary Neoplasms; adenom; adrenokortikotropní hormon; Adenoma; Adrenocorticotropic Hormone; lidé; retrospektivní studie; Retrospective Studies; prolaktinom; nádory hypofýzy; Humans